1995
DOI: 10.1016/0360-1315(95)00009-b
|View full text |Cite
|
Sign up to set email alerts
|

Remote exploratoriums: Combining network media and design environments

Abstract: Abstract-In an educational context, World Wide Web clients such as NCSA Mosaic ® are of limited value because they put learners in the role of information absorbers. Drawing on a museum analogy, learners using Mosaic can be perceived, similar to museum visitors, as passive observers of exhibits. Despite the richness of exhibits in terms of the amount of information as well as the use of multimedia, activity is restricted to navigation through real (museum) or hyper (Mosaic) spaces. More effective learning woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In our previous work on the Remote Explorium (Ambach, Perrone, & Repenning, 1995) we supported designers of Agentsheets applications by allowing the exchange of entire Agentsheets applications via the Web. Our experience with the Remote Explorium indicated that there was a need to exchange not only whole simulations, but application components of a finer grain, including individual agents.…”
Section: Media For Distributed Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work on the Remote Explorium (Ambach, Perrone, & Repenning, 1995) we supported designers of Agentsheets applications by allowing the exchange of entire Agentsheets applications via the Web. Our experience with the Remote Explorium indicated that there was a need to exchange not only whole simulations, but application components of a finer grain, including individual agents.…”
Section: Media For Distributed Communitiesmentioning
confidence: 99%
“…At the Center for LifeLong Learning and Design, our use of technology in education has focused on blending constructionist systems, in the form of interactive simulations, with the support of network media, such as the WWW (Ambach, Perrone, & Repenning, 1995; Fischer, 1994; Fischer, 1995). Constructionism, based on the constructivist ideas of Piaget that stress that knowledge is constructed from a child's experiences in the world, proposes that people best construct new knowledge when they are engaged in personally meaningful tasks (Papert, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the evolutionary growth phase, the environment developers are not present, thus making end-user modification a necessity rather than a luxury (at least for small-scale evolutionary changes). We have addressed this challenge with end-user modifiability [Eisenberg, Fischer 1994;Fischer, Girgensohn 1990], and end-user programming [Ambach, Perrone, Repenning 1995;Nardi 1993].…”
Section: Seeding Evolutionary Growth Reseeding: the Ser Process Modmentioning
confidence: 99%
“…The Visual AgenTalk Behavior Exchange extends our initial system, called the Remote Explorium [24], by adding different levels of sharing granularity. Using the same tactile manipulation paradigm end users can share entire Agentsheets simulations, individual agents, rules and commands (Figure 4 3 ).…”
Section: Ifmentioning
confidence: 99%